Enantioseparation of the four nadolol stereoisomers by fixed-bed and simulated moving bed chromatography - Arafah, Rami (2019)
In the last decades, the separation and purification of high added value products by liquid chromatography has been a very popular technique. The development of more stable and efficient stationary phases, together with the design of innovative and more flexible separation processes, enhanced the use of chromatographic processes, particularly at preparative and industrial scales through simulated moving bed (SMB) technology and allied techniques. Nowadays, preparative and SMB related techniques are more and more used in the separation of a wide range of high added value products of interest for the pharmaceutical, fine chemistry, biotechnology and food industries. In this context, one of the actual main challenges concerns the design and optimization of these chromatographic processes for multicomponent separations. This includes the development of new and innovative chromatographic processes, combining different design strategies and modes of operation, with different types of stationary and mobile phases. This communication will introduce the multicomponent separation challenge using the commercial pharmaceutical drug of nadolol stereoisomers. The nadolol represents a very interesting case-study of multicomponent chiral separation since it is composed by four stereoisomers, arranged in two pairs of enantiomers. In this way, it introduces the possibility of alternative strategies, using different kind of separation sequences and techniques, the use of different packings (chiral and achiral stationary phases), and the correspondent mobile phase optimization at both normal and reversed phase modes. An extensive set of experimental results obtained at fixed-bed and SMB operations will be presented. The complete methodology will be explained and applied for the pseudo-binary enantioseparation of the more retained and active stereoisomer (1+2+3)/(4), and for the (2)/(3) and (1)/(4) binary enantioseparations after a first achiral pseudo-binary separation of the two nadolol racemates.